Factors Affecting Work Accidents Among Electrical Network Maintenance Workers: A Systematic Literature Review - Hijratul Ullia; Hanifa Maher Denny; Suroto Suroto (Universitas Pahlawan Tuanku Tambusai, 2026)
Work acciden during the electrical maintenance directly affect the health of the employees, productivity losses, and company losses because of lost assets. A number of elements contribute to accidents, and by understanding these aspects, workers can take protective actions before an electrical disaster occurs. The